Synthesis of star-shaped pyrrole-based C3-symmetric molecules via ring-closing metathesis, Buchwald–Hartwig cross-coupling and Clauson–Kaas pyrrole synthesis as key steps. Issue 11 (14th March 2018) - Kotha, Sambasivarao; Todeti, Saidulu; Das, Tarasankar; Datta, Anindya
Graphical abstract: Highlights: Ring-closing metathesis product which underwent aromatization. Photophysical properties of star-shaped molecules are studied. N, N′ -Diallyl C 3 -symmetric product showing more lifetime than pyrrole-based star-shaped derivative. Abstract: We have demonstrated three contrasting synthetic strategies to assemble pyrrole-based C 3 -symmetric molecule. Here, ring-closing metathesis (RCM), Buchwald–Hartwig cross-coupling and Clauson–Kaas pyrrole synthesis have been used as key steps. Interestingly, readily available starting materials such as 4-aminoacetophenone, 4-bromo acetophenone and 4-nitro acetophenone have been used as starting materials. Grubbs' first generation catalyst (G-I) is useful for one-pot RCM and aromatization sequence without the involvement of additional reagents. We also report photophysical properties of these star-shaped molecules.